Knowledge, Attitude, and Support and Motivation Influenced An Initial Nutrition Screening - Hadiyani, Ai; Jus’at, Idrus; Wahidi, Kemala Rita (Alta Dharma Publisher, 2023)
Background: Initial nutritional screening by nurses is the gateway to identifying patients at risk of dietary problems in hospital patients. Objective: The study aimed to analyze the effect of knowledge, attitudes, and hospital management support on nurses' implementation of early nutrition screening through motivation as an intervening variable. Method: The method used in this study is a quantitative method with a cross-sectional approach. Purposive sampling was used in this study. The sample measurement used the G Power application, and the sample size used in this study was 134 respondents. The data analysis method used in this study is multiple linear regression analysis Result: The results of this study indicate that knowledge and hospital management support have a significant effect on the implementation of early nutrition screening. Attitude was not significantly associated with early nutrition screening. Motivate did not mediate the knowledge, attitude, and hospital management support simultaneously on the implementation of early nutrition screening. Conclusion. Improving knowledge and supporting from management were positive effect on implementation of early nutrition screening. However, attitude was not positive effect early nutrition screening. Recommendation. Further study needs to conduct the study in difference population and setting the ensure the finding and need to address the factors associated with implementation of early nutrition screening